2017
DOI: 10.1038/ismej.2017.183
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the relative importance of species sorting and dispersal limitation in shaping marine bacterial versus protist communities

Abstract: A central challenge in microbial ecology is to understand the underlying mechanisms driving community assembly, particularly in the continuum of species sorting and dispersal limitation. However, little is known about the relative importance of species sorting and dispersal limitation in shaping marine microbial communities; especially, how they are related to organism types/traits and water depth. Here, we used variation partitioning and null model analysis to compare mechanisms driving bacterial and protist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
270
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(302 citation statements)
references
References 73 publications
24
270
8
Order By: Relevance
“…More intriguing are our results for protists, given that they presented a low reaction to environmental selection, while in a much more homogeneous environment, such as the open ocean, Wu et al . () found that selection was one of the main community structuring processes. Furthermore, it has been reported a prevalence of selection over other community structuring mechanisms in microbial terrestrial fungi (Morrison‐Whittle and Goddard, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More intriguing are our results for protists, given that they presented a low reaction to environmental selection, while in a much more homogeneous environment, such as the open ocean, Wu et al . () found that selection was one of the main community structuring processes. Furthermore, it has been reported a prevalence of selection over other community structuring mechanisms in microbial terrestrial fungi (Morrison‐Whittle and Goddard, ).…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have compared the action of selection, dispersal and drift on bacterial and protist community structuring. Recently, Wu et al (2018) quantified the role of the previous processes in shaping bacterial and protists communities populating surface waters of the East China Sea. They found that selection was 1.4 times more important than dispersal limitation in bacteria, while we found that selection was approximately 3 times more important than dispersal limitation.…”
Section: Resultsmentioning
confidence: 99%
“…() found that spatial factors were most important for both. Further, it has been shown that assembly mechanisms can differ between habitat generalists and specialists (Szekely and Langenheder, ; Liao et al ., ; Wu et al ., ). The distribution of habitat generalists may be primarily determined by neutral processes because of their general indifference to the variation in habitat conditions, whereas habitat specialists are more strongly assembled by species sorting because of their specific preferences for certain environmental conditions (Liao et al ., ).…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 97%
“…It is, however, hard to draw general conclusions from those studies since widely different results have been obtained, partly perhaps because different definitions of rare and abundant taxa were used: for example, Liao et al (2017) showed that species sorting was the most important assembly mechanism for both rare and abundant taxa, but that different environmental variables were important; Liu et al (2015) found that local environmental factors had a stronger effect on rare lake bacteria as opposed to abundant ones; Niño-Garcia et al (2016b) found rare bacteria to be to a greater extent randomly assembled and, finally, Yang et al (2016) found that spatial factors were most important for both. Further, it has been shown that assembly mechanisms can differ between habitat generalists and specialists (Szekely and Langenheder, 2014;Liao et al, 2016;Wu et al, 2018). The distribution of habitat generalists may be primarily determined by neutral processes because of their general indifference to the variation in habitat conditions, whereas habitat specialists are more strongly assembled by species sorting because of their specific preferences for certain environmental conditions (Liao et al, 2016).…”
Section: Community Properties and Traitsmentioning
confidence: 99%
“…The hypothesis was recently confirmed by Wu et al . () who proposed the underlying reason to be stronger metabolic plasticity and higher dispersal abilities of bacteria due to their smaller size, as compared with the microeukaryotes.…”
Section: Discussionmentioning
confidence: 99%